1987
DOI: 10.1111/j.1570-7458.1987.tb01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal chromenes from the Asteraceae: structure-activity relations

Abstract: Chromenes (benzopyrans), common to many genera of the Asteraceae, are lethal to the neonate variegated cutworm, Peridrorna saucia Hiibner, when presented on the inner walls of glass vials at concentrations of 1.0 #mol/vial or less. Closely related benzofurans, including some from the same plants, are relatively inactive at these concentrations. The most potent of seven naturally-occurring and four derived chromenes is the well known allatocidin, precocene II, with an LDs0 of 0.134 t~mol/vial or 0.67 #g/cm 2. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The chrornenes from Piper hostmamianurn [46], an amazonian shrub, are structurally similar to chromenes from members of the Asteraceae which are phototoxic to various microbes [47] and insects [47,48]. Studies are under way to determine the identity of the antimicrobial metabolites in the genus Piper, and whether they are effective insecticides as is the ease with many other plant-derived phototoxins (see [l-31 and [14] for discussions of the broadspectrum toxicity of plant phototoxins).…”
Section: Resultsmentioning
confidence: 99%
“…The chrornenes from Piper hostmamianurn [46], an amazonian shrub, are structurally similar to chromenes from members of the Asteraceae which are phototoxic to various microbes [47] and insects [47,48]. Studies are under way to determine the identity of the antimicrobial metabolites in the genus Piper, and whether they are effective insecticides as is the ease with many other plant-derived phototoxins (see [l-31 and [14] for discussions of the broadspectrum toxicity of plant phototoxins).…”
Section: Resultsmentioning
confidence: 99%
“…Vulgarone B has been reported as a gastropod repellant, and this has led us to test it for the molluscicidal activity 6. Plants in the family Asteraceae possess compounds with many biological activities, including phytotoxic, antifungal and insecticidal activities 7–11. Our preliminary bioassay of vulgarone B and the steam‐distilled oil of A douglasiana indicated lethal activity against P trivolvis .…”
Section: Introductionmentioning
confidence: 87%
“…), is insecticidal to a wide range of insect species [3-61, including some considered insensitive to the antihormonal effects of the precocenes. In our previous investigations of structureactivity relations for the insecticidal actions of acetylchromenes [6,7], we found that compounds possessing free hydroxyl groups were significantly less toxic to both cutworms and grasshoppers. In particular, the 7-demethyl derivative of encecalin (2) is significantly less toxic than encecalin in insects from four different orders so far tested [4-61. In the present report, we investigate differences in pharmacokinetics and metabolism between encecalin and DME* in the migratory grasshopper, Melanoplus sanguinipes.…”
Section: Introductionmentioning
confidence: 89%